Analisa Beban Kerja Mental Menggunakan Metode NASA-TLX Pada Divisi Operation PT Z - Azzahra, Anisa; Nugraha, Asep Erik (Universitas Indraprasta PGRI Jakarta, 2025)
Operations division employees in the telecommunications industry often face high mental workloads due to complex tasks, tight deadlines, and demands for accuracy and speed in their work. Excessive mental workload risks causing stress and reducing productivity. This research aims to evaluate the level of mental workload of PT Z operations division employees using the NASA-TLX method. NASA-TLX measures workload based on six main aspects: Mental Demand, Physical Demand, Temporal Demand, Performance, Effort, and Frustration Level. Data collection was carried out through questionnaires, then analyzed to obtain the average Workload Weighting Level (WWL). The results of the analysis show that the average WWL value is 74.61, which is categorized as high. The main factors contributing to high mental workload include task uncertainty, tight deadlines, long hours working in front of the computer, and intensive multitasking. As corrective steps, this research recommends adjusting workload, providing sufficient rest time, and improving the ergonomics of the work environment. It is hoped that these findings can help companies manage employee workload to improve their welfare and productivity.